Upaya Guru IPS Mengembangkan Aspek Afektif Di Kelas VII SMPN 1 Cilimus - Novi Shafiyaturrohmah; Nasehudin, Nasehudin; Wisnu Hatami (Journal Pendidikan Ilmu Pengetahuan Sosial, 2024)
The background of this research is that learning is a process of changing behavior in schools which includes three aspects, namely cognitive, affective and psychomotor aspects. however, in fact changes in attitude or behavior only touch the cognitive aspect, namely in completing the material and . mastering the material, the formation of student attitudes is an aspect that is no less important.This study aims to explain and find out the implementation of learning by social studies teachers, the condition of the students' affective aspects, and the efforts of social studies teachers in developing affective aspects in Class VII SMPN 1 Cilimus Kab. KuninganThis affective aspect is urgent or very important to study, the affective aspect will make the teaching and learning process more directed, without constraints and meaningful. Given the importance of a teacher in teaching and educating, especially in the affective aspects or parts of the values ​​in students' lives and personality development, appropriate techniques are needed.This type of qualitative research with descriptive methods with data collection techniques is observation, interviews, and documentation. The subjects of the research were the vice curricula, social studies teachers and students. Data analysis techniques, data reduction, data presentation, and drawing conclusions, test the validity of the data using data validity and data triangulation techniques.In this study, the results of research on developing affective aspects in class VII.9 of SMP Negeri 1 Cilimus were carried out by social studies teachers to improve the quality of learning. In the affective aspect of students there are still students who are not focused on learning, student responses lack active participation, values (values) are willing to apply the values taught and are able to apply them to themselves in everyday life. Social studies teachers' efforts in developing affective aspects by transforming affective values ​​in the learning process by getting used to greeting, praying, checking the tidiness of how to dress and class cleanliness. Integrating characters in social studies learning, namely, religion, tolerance, discipline, peace-loving and responsible. Programs - School programs and teachers carry out habituation of noble character with dhuha prayer activities, reading yasin and asmaul husna. The teacher's efforts to provide support by motivating students in learning and the importance of the teacher's efforts to become role modeling in schools.